IELTS Common mistakes for bands 60.-7.0 : Julie Moore. - Moore, Julie, ....- (Cambridge : Cambridge University Press, 2020)
This handy little book highlights the real mistakes students make in the IELTS test and shows how to avoid them. Suitable for both IELTS Academic and IELTS General Training, it's perfect for students aiming for bands 6.0-7.0. Each unit targets a key problem area. IELTS-style exercises with clear explanations show you how to use the language accurately to achieve your target band score, and you can check what you've learned in the units with regular tests. Previous title Common Mistakes at IELTS Advanced.
Keywords: Engels taalgebruik